Medicinal flora of the baiku yao people - An ethnobotanical documentation in South China - Tingting Li; Binsheng Luo; Yuanming Tong; Guiyuan Wei; Ling Chai; Renchuan Hu (BMC, 2024)
Abstract Background This study explores the medicinal plant knowledge of the Baiku Yao, a unique ethnic group in China. Despite existing research on their ethnobotanical practices, a comprehensive understanding of their medicinal flora remains lacking. This study aims to document and analyze the species distribution, utilization, and traditional knowledge of medicinal plants used by Baiku Yao. Methods Ethnobotanical surveys were conducted in various Baiku Yao villages across different seasons from 2019 to 2023. Informants were interviewed, and plant specimens were collected and identified. Statistical analyses, including the Relative Frequency of Citation (RFC), were employed to understand plant importance in Baiku Yao culture. Results In an ethnobotanical survey conducted in the Baiku Yao region, 434 medicinal plant species were documented, highlighting significant ethnobotanical diversity and a deep cultural integration of traditional medicinal practices. The study revealed pronounced geographical variations in plant knowledge among villages, with a notable reliance on wild plants, as 85.48% were sourced from the wild, reflecting unique local ethnobotanical knowledge. Predominantly herbs and shrubs were used due to their accessibility and abundance in the local environment. High Relative Frequency of Citation (RFC) values for certain species underscored their importance for local health needs and additional economic value. The utilization of various plant parts, particularly whole plants, roots, and leaves, indicates a holistic approach to medicinal applications, adapted to combat prevalent health issues such as skin and infectious diseases. The study also uncovered the Baiku Yao's cultural practices for countering "Gu" afflictions-a range of pathogenic conditions-with 18 diverse antidote plants used for skin, digestive, and musculoskeletal disorders. The study underscores the imperative of preserving this rich medicinal heritage through innovative models that engage youth and leverage new media, ensuring the inheritance and evolution of Baiku Yao's traditional knowledge. Conclusions Baiku Yao's medicinal plant use reflects a deep, culturally ingrained knowledge, closely tied to local ecology. The study highlights the importance of preserving this unique ethnobotanical heritage and suggests interdisciplinary approaches for future research.